2014
DOI: 10.3109/00365521.2014.880182
|View full text |Cite
|
Sign up to set email alerts
|

Role of small intestinal bacterial overgrowth in severe small intestinal damage in chronic non-steroidal anti-inflammatory drug users

Abstract: OBJECTIVE. Enteric bacteria play a significant role in the pathogenesis of non-steroidal anti-inflammatory drug (NSAID)-induced small intestinal damage. However, the association between small intestinal bacterial overgrowth (SIBO) and NSAID-induced small intestinal damage remains unclear. The aim of the study was to examine the association between SIBO and the presence of NSAID-induced severe small intestinal damage or its symptoms in chronic NSAID users. MATERIALS AND METHODS. Forty-three patients who had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
18
0
3
Order By: Relevance
“…We assessed the association between the severity of NSAID-induced small intestinal damage and bacterial overgrowth measured by lactulose hydrogen breath test (LHBT) in patients with rheumatoid arthritis and osteoarthritis using NSAIDs for more than 3 months [21]. Our results showed that LHBT-positive patients were significantly associated with an increased odds ratio for severe NSAID-induced small intestinal damage.…”
Section: Significance Of Dysbiosis In Nsaid-induced Small Intestinal mentioning
confidence: 80%
“…We assessed the association between the severity of NSAID-induced small intestinal damage and bacterial overgrowth measured by lactulose hydrogen breath test (LHBT) in patients with rheumatoid arthritis and osteoarthritis using NSAIDs for more than 3 months [21]. Our results showed that LHBT-positive patients were significantly associated with an increased odds ratio for severe NSAID-induced small intestinal damage.…”
Section: Significance Of Dysbiosis In Nsaid-induced Small Intestinal mentioning
confidence: 80%
“…By using a lactulose hydrogen breath test, small bowel bacteria overgrowth was found in 59% of users with severe small bowel damage compared with only 24% of users without severe small bowel damage. 15 To further support the pathogenetic role of bacteria in NSAID enteropathy, several studies reported that antibiotics such as ampicillin and metronidazole alleviated the severity of NSAID-induced small bowel damage. 12,14 Some probiotics (eg, Lactobacillus casei) have been reported to reduce small bowel mucosal inflammation and permeability induced by NSAIDs.…”
Section: Role Of Bacteria In Nonsteroidal Anti-inflammatory Drug Entementioning
confidence: 98%
“…В кли-ническом исследовании, проведенном в Японии с использова-нием капсульной эндоскопии и определением содержания во-дорода в выдыхаемом воздухе (дыхательный тест с лактулозой), обнаружили избыточный рост бактерий в тонкой кишке в 24% случаев нетяжелых энтеропатий, обусловленных приемом НПВП, и 59% -тяжелых форм патологии. Положительный ды-хательный тест с лактулозой у пациентов, получавших НПВП, повышал вероятность диагностики тяжелого повреждения тон-кой кишки с ОШ 6,54 (при 95% ДИ от 1,40 до 30,5) [56].…”
Section: терапевтический архив 12 2014unclassified